The forbidden garden : the botanists of besieged Leningrad and their impossible choice - Parkin, Simon (Scribner, 2024)
"In the summer of 1941, German troops surrounded the Russian city of Leningrad-now St. Petersburg-and began the longest blockade in recorded history, one that would ultimately claim the lives of nearly three-quarters of a million people. At the center of the besieged city stood a converted palace that housed the world's largest collection of seeds-more than 250,000 samples hand-collected over two decades from all over the globe by world-famous explorer, geneticist, and dissident Nikolai Vavilov, who had recently been disappeared by the Soviet government. After attempts to evacuate the priceless collection failed and supplies dwindled amongst the three million starving citizens, the employes at the Plant Institute were left with a terrible choice. Should they save the collection? Or themselves? These were not just any seeds. The botanists believed they could be bred into heartier, disease-resistant, and more productive varieties suited for harsh climates, therefore changing the future of food production and preventing famines like those that had plagued their countrymen before. But protecting the seeds was no idle business. The scientists rescued potato samples under enemy fire, extinguished bombs landing on the seed bank's roof, and guarded the collection from scavengers, the bitter cold, and their own hunger. Then in the war's eleventh hour, Nazi plunderers presented a new threat to the collection... Drawing from previously unseen sources, award-winning journalist Simon Parkin-who has "an inimitable capacity to find the human pulse in the underbelly of war" (The Spectator)-tells the incredible true story of the botanists who held their posts at the Plant Institute during the 872-day siege and the remarkable sacrifices they made in the name of science"--